Fooled by randomness : the hidden role of chance in life and in the markets - Taleb, Nassim Nicholas, 1960- (New York : Penguin Books, 2004)
This work has shaken Wall Street thanks to its contention that much of what people perceive as skill playing the markets is often nothing more than luck.
pt. III. Wax in my ears : living with randomitis -- I am not so intelligent -- Wittgenstein's ruler -- The Odyssean mute command -- 12. Gamblers' ticks and pigeons in a box -- Taxi-cab English and causality -- The Skinner pigeon experiment -- Philostratus redux -- 13. Carneades comes to Rome : on probability and skepticism -- Carneades comes to Rome -- Probability, the child of skepticism -- Monsieur de Norpois' opinions -- Path dependence of beliefs -- Computing instead of thinking -- From funeral to funeral -- 14. Bacchus abandons Antony -- Notes on Jackie O.'s funeral -- Randomness and personal elegance -- Epilogue. Solon told you so -- Beware the London traffic jams -- Postscript. Three afterthoughts in the shower -- First thought : the inverse skills problem -- Second though : on some additional benefits of randomness -- Uncertainty and happiness -- The scrambling of messages -- Third thought : standing on one leg -- Acknowledgments for the first edition -- A trip to the library : notes and reading recommendations -- Notes -- References -- Index.
Originally published : New York : Thomson/Texere, 2004.
Includes bibliographical references : (pages 293-306) and index.
Keywords: Investments; Chance; Random variables